Rhinovirus-induced asthma exacerbations and risk populations. Issue 2 (April 2016) - Coleman, Laura; Laing, Ingrid A.; Bosco, Anthony
Abstract : Purpose of review: This article discusses recent findings into the mechanisms that determine how viruses trigger asthma exacerbations. Recent findings: Substantial progress has been made in our understanding of the pathogenesis of virus-induced asthma exacerbations. This includes new insights into the role of bacteria, the regulation of interferon responses, and the discovery of innate immune pathways that link viral infections with allergic inflammation. Progress has also been made in elucidating the genetic risk factors for asthma exacerbations, most notably the contribution of the ORMDL3/GSDMB locus on 17q, the mechanisms underlying the farming effect, and the discovery that CDHR3 binds to rhinovirus species C. Summary: Asthma exacerbations are heterogeneous conditions that involve the complex interplay between environmental exposures and innate and adaptive immune function in genetically predisposed individuals. Recent insights into the interrelationships between these factors provide new opportunities for therapeutic intervention.